Front Cover. Issue 3 (8th February 2020) - Liao, Ziyan; Zhang, Lin; Nobis, Michael P.; Wu, Xiaogang; Pan, Kaiwen; Wang, Keqing; Dakhil, Mohammed A.; Du, Mingxi; Xiong, Qinli; Pandey, Bikram; Tian, Xianglin
Abstract : The cover image is based on the Original Article Climate change jointly with migration ability affect future range shifts of dominant fir species in Southwest China by Kaiwen Pan et al., https://doi.org/10.1111/ddi.13018 .